Use of the Puccinia sorghi haustorial transcriptome to identify and characterize AvrRp1-D recognized by the maize Rp1-D resistance protein. - Saet-Byul Kim; Ki-Tae Kim; Solhee In; Namrata Jaiswal; Gir-Won Lee; Seungmee Jung; Abigail Rogers; Libia F Gómez-Trejo; Sujan Gautam; Matthew Helm; Hee-Kyung Ahn; Hye-Young Lee; et al. (PLoS Pathogens)
The common rust disease of maize is caused by the obligate biotrophic fungus Puccinia sorghi. The maize Rp1-D allele imparts resistance against the P. sorghi IN2 isolate by initiating a defense response that includes a rapid localized programmed cell death process, the hypersensitive response (HR). In this study, to identify AvrRp1-D from P. sorghi IN2, we employed the isolation of haustoria, facilitated by a biotin-streptavidin interaction, as a powerful approach. This method proves particularly advantageous in cases where the genome information for the fungal pathogen is unavailable, enhancing our ability to explore and understand the molecular interactions between maize and P. sorghi. The haustorial transcriptome generated through this technique, in combination with bioinformatic analyses such as SignalP and TMHMM, enabled the identification of 251 candidate effectors. We ultimately identified two closely related genes, AvrRp1-D.1 and AvrRp1-D.2, which triggered an Rp1-D-dependent defense response in Nicotiana benthamiana. AvrRp1-D-induced Rp1-D-dependent HR was further confirmed in maize protoplasts. We demonstrated that AvrRp1-D.1 interacts directly and specifically with the leucine-rich repeat (LRR) domain of Rp1-D through yeast two-hybrid assay. We also provide evidence that, in the absence of Rp1-D, AvrRp1-D.1 plays a role in suppressing the plant immune response. Our research provides valuable insights into the molecular interactions driving resistance against common rust in maize.